Secondary metabolite induced tolerance to Fusarium oxysporum f.sp. cubense TR4 in banana cv. Grand Naine through in vitro bio-immunization: a prospective research translation from induction to field tolerance - Damodaran, T; Mishra, Maneesh; Muthukumar, M; Rajan, Shailendra; Yadav, Kavita; Kumar, Alok; Debnath, Prasenjit; Kumari, Sangeeta; Bora, Popy; Gopal, Ram; Kumar, Sandeep (Frontiers in Microbiology, 2023)
An innovative tissue culture mediated incorporation of metabolite-based biomolecule (Bio-immune) at in vitro stage itself in banana cv. Grand Naine was developed and validated for the production of Fusarium oxysporum f.sp. cubense TR4 tolerant plantlets. The novel bio-immune formulation developed by us, exhibited a significant antifungal potency against Foc TR4 with a high percent inhibition (100%) at a 2.5% concentration of bio-immune on the 5th, 7th, and 9th DAI. Bio-immune integrated during in vitro shoot proliferation stage in banana cv. Grand Naine recorded significant enhancement in the growth of roots and shoots. Bio-immune (0.5%) fortified media produced 12.67 shoots per clump whereas control registered only 9.67 shoots per clump. Similarly, maximum root numbers (7.67) were observed in bio-immune plants which were significantly higher over control (5.0). The bio-immunized banana transplants recorded a higher survival rate (97.57%) during acclimatization as compared to the control (94.53%). Furthermore, evaluation of the bio-immunized plants in pot experiments revealed that unimmunized plants treated with FocTR4 (TF) exhibited mortality between 60 and 90 days. On the 90th day after planting, a high mean disease severity index (DSI) of 3.45 was observed with unimmunized plantlets while the bio-immunized plants (TFBI) and ICAR-FUSICONT treated plants (TFTR) showed substantially reduced DSI (0.20 and 1.00) compared to FocTR4 treated control (TF). Significant increases in polyphenol oxidase (PPO), peroxidase (POD), β-1,3-glucanase, phenylalanine ammonia-lyase (PAL), chitinase activities, and enhanced phenol contents were recorded in bio-immunized plants compared to unimmunized plants. Field experiments at two different locations in Bihar, India revealed that bunch weight, no. of hands/bunch, and no. of fingers/hand of bio-immune treated plants were significantly higher compared to the control.